Efeitos do ensino explícito da gramática no desenvolvimento de diferentes tipos de propriedades em L2 - Teixeira, Joana (Revista da Associação Portuguesa de Linguística, 2020)
The present study investigates the effects of explicit grammar teaching on the acquisition of a core syntactic property (the ungrammaticality of free inversion) and a syntax-discourse property (the unacceptability of locative inversion with informationally heavy verbs) by advanced and upper intermediate Portuguese learners of English. The study followed a pre-test/post-test design. Its results reveal that, at an upper intermediate level, explicit teaching did not have any effects on learners’ performance, regardless of the type of property. At an advanced level, in contrast, the teaching intervention resulted in gains in all cases. However, these gains were only maintained beyond the immediate teaching period when the target property was strictly syntactic. These findings indicate that the effectiveness of instruction depends on the stage of development at which learners are and on the type of target property. The pedagogical implications of the findings are discussed in detail.